Herpes Zoster After Tocilizumab Therapy in COVID-19 Survivor: A Case Report - Suwenny Suwenny; Sahat Halim (Interna Publishing, 2022)
The COVID-19 pandemic has become a concern for the world community. However, despite abundant attempts taking place, there is currently no definitive therapy for COVID-19 yet. The clinical approaches recently adopted are the provision of antiviral therapy and immunomodulators. One of the immunomodulators that are currently being researched is tocilizumab, an IL-6 receptor antagonist monoclonal antibody. Many case studies and retrospective observational studies have shown that there is a chance that tocilizumab could diminish death rates in COVID-19 patients with severe or critical symptoms. Along with the growing use of tocilizumab in the COVID-19 cases that are emergent in nature, the occurrence of unpredictable adverse effects of the drugs have also been raising.  This case report describes a COVID-19 confirmed patient with severe symptoms who was given tocilizumab in addition to standard therapy. The patient developed Herpes Zoster infection which was suspected to be related to the adverse effects of using tocilizumab, which is known for its likelihood to increase the risk of new infections and also probably reactivate latent infections. Tocilizumab use seems to be effective in combating cytokine storm associated with severe COVID-19 infection. The possibility of serious adverse effects in the utilization of tocilizumab, though rare, cannot be excluded. The presence of a latent or chronic infection that can undergo reactivation should be a consideration for appropriate screening or prophylaxis before administering tocilizumab.